Influence of socio-economic conditions and maternal knowledge in self-effectiveness for prevention of childhood diarrhea - Rhaiany Kelly Lopes de Oliveira; Brena Shellem Bessa de Oliveira; Jallyne Colares Bezerra; Maria Jocelane Nascimento da Silva; Francisca Mayra de Sousa Melo; Emanuella Silva Joventino (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To verify the association among socioeconomic conditions, maternal behaviors and knowledge with their self-efficacy to prevent childhood diarrhea. Method: Analytical, quantitative study. Interviews were conducted with 238 mothers of children under five admitted into a hospital from January to April 2016. Were collected Sociodemographic data, maternal knowledge on prevention and management of childhood diarrhea, and application of the Maternal Self-Efficacy Scale for Childhood Diarrhea. Results: Association between socioeconomic and maternal self-efficacy variables: family income (p = 0.049), child age (p = 0.010), house type (p = 0.042), garbage destination (p = 0.037), sewage (p = 0.016) and sanitary type (p = 0.006). Regarding knowledge about causes of diarrhea: warmth/heat (p = 0.021); dentition (p = 0.030). Association between self-efficacy and preventive behaviors: home hygiene (p = 0.023); breastfeeding practice (p = 0.028). Conclusion: Socioeconomic conditions and knowledge presented by mothers can influence the level of maternal self-efficacy for the prevention of childhood diarrhea.